Utilization of Endemic Fruits in Efforts to Conserve Genetic Resources in Jayapura District - Mariana Ondikeleuw; Bau Mene; Merlin K. Rumbarar; M. Nikmatulah; Klementin Fairyo; Sonya M. Kawer; Edoward Krisson Raunsay; Fenky Marsandi; Riska Ayu Purnamasari (Postgraduate, University of Mataram, 2024)
Papua is known as an island rich in plant diversity and potential fauna. The problems encountered are that not all types of genetic resources have been explored and identified, limited guidance on the characterization of local plants and some of them are also starting to be difficult to find, especially species that experience rarity and lead to extinction. This study aims to explore and introduce the potential of typical Papuan fruit plants so that it is useful for policymakers for the development of typical fruit plants in the future as a food reserve source of vitamins, and minerals. The location was determined based on where typical fruit plants grow in Papua Province. Data collected include socio-cultural data (local wisdom), its contribution to the economy of farmer households, and growing environment data. The research method used was descriptive exploration, to be able to document community knowledge about the management of typical fruit germplasm requires appropriate information gathering and careful and in-depth study. Information was taken in the yard and land outside the yard/farmer's garden. Activities were carried out from March to December 2019 in Jayapura district. Local plants include fruit plants endemic to the local community, which have been used for generations by the local community.